1999
DOI: 10.1016/s0895-7061(99)00049-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypertension and its treatment on lipid, lipoprotein(a), fibrinogen, and bilirubin levels in patients referred for dyslipidemia

Abstract: We measured the serum lipid profile, together with plasma fibrinogen and serum lipoprotein(a) (Lp[a]), glucose, bilirubin, and albumin levels in 491 patients (310 men) who were referred for the management of primary dyslipidemia. All these variables have been shown to predict vascular events. The patients were not taking lipid-lowering drugs; hypertension was present in 156 (31.7%) of them. Of the hypertensive patients, 52 (33%) were not receiving any treatment to control their blood pressure. This omission wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…31,32 For example, ACEIs and statins can have beneficial effects on haemostatic and other factors. [33][34][35][36] Moreover, it has been shown that treatment with ACEIs 37,38 and statins 39,40 improved vasodilatation and decreased vascular damage. A significant additive effect on structural vascular damage, blood pressure, and vascular resistance was also shown during combination treatment of simvastatin and enalapril in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 For example, ACEIs and statins can have beneficial effects on haemostatic and other factors. [33][34][35][36] Moreover, it has been shown that treatment with ACEIs 37,38 and statins 39,40 improved vasodilatation and decreased vascular damage. A significant additive effect on structural vascular damage, blood pressure, and vascular resistance was also shown during combination treatment of simvastatin and enalapril in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Other Ang II receptor blockers or antihypertensive drugs may not share the 'specific' TXA 2 -inhibiting property of losartan if their struc-ture does not include an imidazole group. The additional anti-thrombotic properties of antihypertensive drug [30][31][32][33][34][35] may influence prescribing habits. Platelet responses to Ang II may reflect the changes occurring in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown, in a small study, that bilirubin levels were lower in untreated hypertensive individuals compared with normotensive people or treated hypertensive patients. We attributed this effect to the antioxidant actions of certain drugs used to treat hypertension and to a higher level of oxidative stress in untreated hypertensive patients [10]. These studies suggest that commonly used drug treatments (i.e.…”
Section: Fieldmentioning
confidence: 89%